KARAKTERISTIK DEWAN KOMISARIS DAN AUDITOR - Eunik, Eunik (Jurnal Akuntansi Bisnis, 2015)
The financial report is a media that company uses to deliver financial information to external parties. In maintaining the quality of the financial statements, the role of the auditor is needed to bridge the gap between the interests of the principals with the agent. Previous researches found that auditor quality has a great impact on reported earnings. Auditors who have specialized industry can offer a higher quality audit compared with non-specialists. This study predict that experience in a particular industry are closely related to the auditor's ability to detect fraud. Using firms listed on Indonesia Stock Exchange of 2008-2012 period, this study shows that board size, firms size, ROA positivele effect auditor industry specialization choice and the ratio of debt negatively affect the auditor industry specialization